Patients' and surgeons' perspectives on the scar components after inferior pedicle breast reduction surgery - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Background: Scarring is the most frequent cause of dissatisfaction both for the surgeons and for the patients in breast reduction surgery. Some of the techniques used today use the classic inverted T scar. An inverted T scar is a combination of three separate scars (periareolar, vertical, and inframammary). To the authors' knowledge, no study has investigated the cosmetic outcome of these three scar components separately. The aim of this study was to determine the surgeons' and patients' perspectives on the cosmetic outcome of these three scar components. Methods: A total of 19 patients who had inferior pedicle reduction mammaplasties were included in the study. The patients' perspectives on their reduction mammaplasty scars and the surgeons' evaluations of scar hypertrophy, widening, and color match were assessed by Likert scales. Results: Patient evaluations revealed that periareolar scars were the most pleasing, whereas the inframammary scars were the least pleasing. Surgeon evaluations revealed no significant difference in scar hypertrophy, color match, or widening for the three scar components. However, the vertical scar had a tendency to widen and the inframammary scar color tended to match poorly. Conclusions: In this study, patients were most pleased with the periareolar scars and least pleased with the inframammary scars. Surgeons need to find ways of getting rid of the inframammary scar and should also deal with vertical scar widening. Scar hypertrophy was not a problem in this patient population.
Keywords: QUALITY-OF-LIFE; OUTCOME ANALYSIS; MAMMAPLASTY; SATISFACTION; MAMMAPALSTY; MACROMASTIA; SYMPTOMS; WOMEN